Generating Energy from Air: Solid State Planar Concentration Cell Based on Graphene Oxide. Issue 8 (5th September 2016) - Wei, Di
Abstract : The first attempt to generate decent energy using the fast transported water molecules and hydrated cations inside graphene oxide (GO) is presented. GO energy source is fully writable and printable, providing very safe energy source to enable new applications otherwise traditional battery technology cannot make including, for example, providing a foldable energy source and platform for futuristic wearable electronics.